Coins and power in late Iron Age Britain - Creighton, John 1964- (New studies in archaeology, 2000)
Cunobelin, Shakespeare's Cymbeline, ruled much of south-east Britain in the years before Claudius' legions arrived, creating the Roman province of Britannia. But what do we know of him and his rule, and that of competing dynasties in south-east Britain? This book examines the background to these, the first individuals in British history. It explores the way in which rulers bolstered their power through the use of imagery on coins, myths, language and material culture. After the visit of Caesar in 55 and 54 BC, the shadow of Rome played a fundamental role in this process. Combining the archaeological, literary and numismatic evidence, John Creighton paints a vivid picture of how people in late Iron Age Britain reacted to the changing world around them